Understanding and optimizing Evolon® CR for varnish removal from oil paintings - Baij, Lambert; Liu, Chun; Buijs, Jesse; Alvarez Martin, Alba; Westert, Dorien; Raven, Laura; Geels, Norbert; Noble, Petria; Sprakel, Joris; Keune, Katrien (Heritage science, 2021)
Evolon ® CR is increasingly used in paintings conservation for varnish removal from oil paintings. Its key benefits over traditional cotton swabs are limiting solvent exposure and reducing mechanical action on the paint surface. However, this non-woven microfilament textile was not originally engineered for conservation use and little is known about its chemical stability towards organic solvents. Moreover, the physical processes of solvent loading and release by Evolon ® CR, as well as solvent retention inside paint after cleaning, have not been studied. These three topics were investigated using a multi-analytical approach, aiming for an improved understanding and optimized use of Evolon ® CR for varnish removal. Our results show that the tissue is generally chemically and physically stable to organic solvents when exposed on timescales that are typical in conservation practice. However, a pre-treatment step of Evolon ® CR is necessary to avoid the release of unwanted saturated fatty acids into the paint during varnish removal. We show that the primary mechanism of solvent uptake by the fibers is ad sorption rather than ab sorption and that the dominant factor dictating the maximum solvent load is the volume of the voids between the fibers. Finally, solvent induced dynamics after application of solvent-loaded Evolon ® CR within the paint film was monitored using portable laser speckle imaging on model paints. A method to quantify solvent-retention in real-time was developed and revealed that the presence of varnish on paintings results in lower dynamics of solvents within the paint in comparison to unvarnished paint. Comparing various solvents, it was found that cleaning with acetone resulted in a roughly six-fold increase in dynamics compared to ethanol and isopropanol.